Calcium/magnesium intake ratio, but not magnesium intake, interacts with genetic polymorphism in relation to colorectal neoplasia in a two‐phase study. Issue 10 (31st August 2015) - Zhu, Xiangzhu; Shrubsole, Martha J.; Ness, Reid M.; Hibler, Elizabeth A.; Cai, Qiuyin; Long, Jirong; Chen, Zhi; Li, Guoliang; Jiang, Ming; Hou, Lifang; Kabagambe, Edmond K.; Zhang, Bing; et al.
Abstract : Some studies suggest that the calcium to magnesium ratio intakes modify the associations of calcium or magnesium with risk of colorectal adenoma, adenoma recurrence, and cancer. Parathyroid hormone (PTH) plays a key role in the regulation of homeostasis for both calcium and magnesium. We hypothesized that polymorphisms in PTH and 13 other genes may modify the association between the calcium/magnesium intake ratio and colorectal neoplasia risk. We conducted a two‐phase study including 1336 cases and 2891 controls from the Tennessee Colorectal Polyp Study. In Phase I, we identified 19 SNPs that significantly interacted with the calcium/magnesium intake ratio in adenoma risk. In Phase II, rs11022858 in PTH was replicated. In combined analysis of phases I and II, we found high calcium/magnesium intake ratio tended to be associated with a reduced risk of colorectal adenoma ( P for trend, 0.040) among those who carried the TT genotype in rs11022858. In stratified analyses, calcium intake (≥ 1000 mg/d) was significantly associated with 64% reduced adenoma risk (OR = 0.36 (95% CI : 0.18–0.74)) among those homozygous for the minor allele (TT genotype) ( P for trend, 0.012), but not associated with risk in other genotypes (CC/TC). Conversely, we found that highest magnesium intake was significantly associated with 27% reduced risk (OR = 0.73 (95% CI : 0.54–0.97)) of colorectal adenoma ( P for trend, 0.026) among those who possessed the CC/TC genotypes, particularly among those with the TC genotype, whereas magnesium intake was not linked to risk among those with the TT genotype. These findings, if confirmed, will help for the development of personalized prevention strategies for colorectal cancer. © 2015 Wiley Periodicals, Inc.